Aerobic Oxidations in Asymmetric Synthesis: Catalytic Strategies and Recent Developments - Kananovich, Dzmitry; Elek, Gábor Zoltán; Lopp, Margus; Borovkov, Victor (Frontiers in Chemistry, 2021)
Despite the remarkable advances in the area of asymmetric catalytic oxidations over the past decades, the development of sustainable and environmentally benign enantioselective oxidation techniques, especially with the efficiency level similar to natural enzymes, still represents a challenge. The growing demand for enantiopure compounds and high interest to industry-relevant green technological advances continue to encourage the research pursuits in this field. Among various oxidants, molecular oxygen is ubiquitous, being available at low cost, environmentally benign and easy-to-handle material. This review highlights recent achievements in catalytic enantioselective oxidations utilizing molecular oxygen as the sole oxidant, with focus on the mechanisms of dioxygen activation and chirogenesis in these transformations.